THE EFFECT OF ROLE PLAYING AND SNOWBALL THROWING LEARNING MODEL ON STUDENTS’ SPEAKING SKILL AT GRADE III ELEMENTARY SCHOOL IN GUGUS RA KARTINI - Yusmi; Su‘ad; Murtono (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to describe the influence of role playing and snowball throwing learning models on students’ speaking skills at third grade elementary school in RA Kartini cluster. This research was an experimental research. The population in this study were students at grade III of elementary schools in RA Kartini cluster. From this population, the research samples were 60 grade III elementary school students. Data collection techniques included giving questionnaires, observation, and documentation. The final analysis utilized descriptive analysis and inferential analysis. Inferential analysis was coducted by operating independent sample t-test to determine the influence role playing and snowball throwing models. The results of the analysis of the first hypothesis test between the role playing class and the conventional class showed a significance value of 0.000 (0.000 < 0.05) and the tcount value was 3.943, while the ttable value was 2.024 (3.943 > 2.024), meaning that Ha1 was accepted. This indicated that role paying had an effect on speaking skills. The second hypothesis test between the snowball throwing class and the conventional class showed a significance value of 0.02 (0.02 < 0.05) and the t-count value of 3.370, while the t-table value was 2.024 (3.370 > 2.024), meaning that Ha2 was accepted. This confirmed that the snowball model throwing significantly influenced the students’ speaking skills. The third hypothesis test showed that between the role playing and snowball throwing learning models, the significance value of speaking skills was 0.017 (0.017 < 0.05) and the t-count value was 2.498 while the ttable value was 2.024 (2.498 > 2.024). Referring to the hypothesis testing, Ha was accepted and Ho3 was rejected while Ha3 was accepted. Thus, it was concluded that role playing learning model was more influential than snowball throwing learning on the students’ speaking skills at the second grade of elementary school in Gugus RA Kartini.